The Road to Better Management in Resistant Hypertension-Diagnostic and Therapeutic Insights - Elisabeta Bădilă; Cristina Japie; Emma Weiss; Ana-Maria Balahura; Daniela Bartoș; Alexandru Scafa Udriște (MDPI AG, 2021)
Resistant hypertension (R-HTN) implies a higher mortality and morbidity compared to non-R-HTN due to increased cardiovascular risk and associated adverse outcomes-greater risk of developing chronic kidney disease, heart failure, stroke and myocardial infarction. R-HTN is considered when failing to lower blood pressure below 140/90 mmHg despite adequate lifestyle measures and optimal treatment with at least three medications, including a diuretic, and usually a blocker of the renin-angiotensin system and a calcium channel blocker, at maximally tolerated doses. Hereby, we discuss the diagnostic and therapeutic approach to a better management of R-HTN. Excluding pseudoresistance, secondary hypertension, white-coat hypertension and medication non-adherence is an important step when diagnosing R-HTN. Most recently different phenotypes associated to R-HTN have been described, specifically refractory and controlled R-HTN and masked uncontrolled hypertension. Optimizing the three-drug regimen, including the diuretic treatment, adding a mineralocorticoid receptor antagonist as the fourth drug, a β-blocker as the fifth drug and an α1-blocker or a peripheral vasodilator as a final option when failing to achieve target blood pressure values are current recommendations regarding the correct management of R-HTN.